PENGETAHUAN DAN KESADARAN MASYARAKAT TENTANG WAJIBNYA PAJAK - Adinda Try Hidayah; Isa Anshori (Jurnal Akuntansi dan Pajak, 2022)
Taxpayer awareness is a condition from which taxpayers know, understand and implement taxes correctly. The higher the level of awareness of taxpayers, the better understanding and implementation of taxes so as to increase tax payments. The purpose of this study was to find out how the level of public knowledge about taxes, the level of public awareness about tax obligations, and the influence of public awareness on national development in Indonesia. Analysis of the factors that influence small and medium business owners in reporting tax obligations in Ceceng going. The results conclude that all factors (knowledge of taxpayers, understanding of taxpayers on tax regulations, perceived benefits of taxpayers from taxes, optimistic attitude of taxpayers towards taxes) have an influence on taxpayer awareness, but the knowledge of taxpayers about taxes has a negative influence. on taxpayer awareness. However, the taxpayer's understanding of tax regulations, the benefits felt by taxpayers from taxes and the taxpayer's optimistic attitude towards taxes have a positive influence on tax awareness. From the results of this study, it can also be seen that the most dominant factor influencing taxpayer awareness is the taxpayer's understanding of tax regulations